Limited effects of an extreme flood event on corals at Ningaloo Reef. (15th May 2017) - Lozano-Montes, Hector M.; Keesing, John K.; Grol, Monique G.; Haywood, Michael D.E.; Vanderklift, Mathew A.; Babcock, Russ C.; Bancroft, Kevin
Abstract: In late April 2014 Ningaloo Reef was exposed to significant freshwater and sediment outflow following an extreme rainfall event (>200 mm in 48 h). It produced a plume of brown water of 9.63 km 2 that was present two days after the rainfall event. The extent of the plume decreased by 55.9% within ten days. Benthic surveys were conducted at eight sites at Ningaloo (three of them within the plume and five outside the plume) using 25 m line transects to assess the percentage cover of all major benthic organisms, including hard corals, soft corals, algae and turf algae. Results from a survey done in May 2014 (approximately one month after the flooding) were compared with one done in March 2014 (before the extreme rainfall event). Corals from the genus Acropora were the dominant species in the coral assemblages surveyed. Our results indicate that percentage cover of Acropora did not vary significantly between sites inside and outside of the plume, but percentage cover of non- Acropora coral varied significantly among plume and non-plume sites. Both patterns were present before the flood. The results show that the flood-induced plumes caused limited damage to the coral along this part of Ningaloo Reef.